2004
DOI: 10.1103/physrevlett.93.175003
|View full text |Cite
|
Sign up to set email alerts
|

Hall Magnetic Reconnection Rate

Abstract: Two-dimensional Hall magnetohydrodynamic simulations are used to determine the magnetic reconnection rate in the Hall limit. The simulations are run until a steady state is achieved for four initial current sheet thicknesses: L=1,5,10, and 20c/omega(pi), where c/omega(pi) is the ion inertial length. It is found that the asymptotic (i.e., time independent) state of the system is nearly independent of the initial current sheet width. Specifically, the Hall reconnection rate is weakly dependent on the initial cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
75
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 16 publications
14
75
1
Order By: Relevance
“…The fraction that reconnect, and end up in the earth's magnetotail, is controlled by the reconnection rate. Assuming this is the Sweet-Parker rate, approximately one in a hundred thousand lines reconnect as opposed to the measured value of one in ten (Hughes, 1995). The predictions of Sweet-Parker strikingly disagree with the observations.…”
Section: A Early History Of Magnetic Reconnection Theorycontrasting
confidence: 44%
See 2 more Smart Citations
“…The fraction that reconnect, and end up in the earth's magnetotail, is controlled by the reconnection rate. Assuming this is the Sweet-Parker rate, approximately one in a hundred thousand lines reconnect as opposed to the measured value of one in ten (Hughes, 1995). The predictions of Sweet-Parker strikingly disagree with the observations.…”
Section: A Early History Of Magnetic Reconnection Theorycontrasting
confidence: 44%
“…The magnetopause is the boundary that separates the geomagnetic field and plasma of terrestrial origin from the solar wind plasma (Hughes, 1995). Figure 8 is a schematic of the magnetosphere showing it on both the dayside and night side.…”
Section: B Magnetic Reconnection In the Magnetospherementioning
confidence: 99%
See 1 more Smart Citation
“…For the three initial magnetic field configurations adopted here, both the magnetic structure and the magnetic energy spectrum have not revealed any significant difference between the low and high ␤ regime. It has been shown that Hall physics is an important ingredient in the development of fast reconnection [42][43][44][45][46][47][48][49][50][51][52] and can have an influence on the linear and nonlinear evolution of the tearing instability. 42,53,54 Future work will include the Hall effect in studying the dynamical evolution of the current sheet.…”
Section: -12mentioning
confidence: 99%
“…The influence of the Hall physics on the reconnection dynamics has been shown in several studies to be dependent on the relation between the Hall parameter c H and the inverse of the Lundqvist number L u . 5,8,22,6 Especially when c H 2 Ͼ L u −1 , the Hall effect has been shown to dominate significantly. It is also shown that the inclusion of the Hall term brings the dynamics of Whistler waves into the system.…”
Section: Discussionmentioning
confidence: 99%